Application of X-rays to dental age estimation in medico-legal practice - Dorota Lorkiewicz-Muszyńska; Agnieszka Przystańska; Tomasz Kulczyk; Anna Hyrchała; Bartłomiej Bartecki; Wojciech Kociemba; Mariusz Glapiński; Marzena Łabęcka; Paweł Świderski (Archives of Forensic Medicine and Criminology, 2015)
Aim of the study: The paper addresses the use of dental age assessment methods based on radiographs in medico-legal practice. Different cases of practical application of the methods are presented including identification of human remains, dental age assessment in a living person and one archaeological case. Material and methods : The study material consisted of cases involving dental age assessment performed in the Department of Forensic Medicine, Poznan University of Medical Sciences in Poznan. Depending on the preliminary assessment of age, the Liversidge or the Kvaal et al. methods were applied. Dental age was estimated on the basis of available pantomograms. In the case of the living person, it was a radiograph supplied for expert evaluation. In the other cases, dental computed tomography was performed. Results : Dental age was successfully estimated in all of the cases. Various methods based on the analysis of X-ray images were applied. Dental age was shown to be correlated with skeletal age. Conclusions : The methods based on radiographs were demonstrated to be useful, and the results they yield are fully correlated with results of anthropological analyses.